2017
DOI: 10.1093/humrep/dex328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulipristal acetate and mifepristone at emergency contraception dose on the embryo-endometrial attachment using an in vitro human trophoblastic spheroid and endometrial cell co-culture model

Abstract: We had free supply of the UPA compound used in this study from Laboratoire HRA Pharma. This work was supported by a Seed Fund from the Centre of Reproduction, Development and Growth, Faculty of Medicine, The University of Hong Kong, Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Then, how does AIF-1 affect endometrial receptivity? In further experiment, we cocultured Ishikawa cells as the endometrial surrogate and JAR cells as the embryo surrogate to simulate the embryo implantation process in vitro (Li et al, 2017) and found that highly expressed AIF-1 could inhibit the adhesion of JAR cells to Ishikawa cells significantly. Adhesion is well known as an important step in trophoblast invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Then, how does AIF-1 affect endometrial receptivity? In further experiment, we cocultured Ishikawa cells as the endometrial surrogate and JAR cells as the embryo surrogate to simulate the embryo implantation process in vitro (Li et al, 2017) and found that highly expressed AIF-1 could inhibit the adhesion of JAR cells to Ishikawa cells significantly. Adhesion is well known as an important step in trophoblast invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa (Human endometrial epithelial cells), Jeg-3 (HTB-36), and AN3 CA (Human endometrial epithelial cells) cells were purchased from American Type Culture Collection (ATCC, USA). The embryo attachment in vitro model was constructed as described previously with minor modifications 24 . Briefly, Ishikawa and Jeg-3 were cultured in DMEM/F-12 medium containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…4 Bc and Cc), as compared to the vector-transfected and non-transfected control cells. However, in-vitro experimental studies using trophoblastic spheroids made from JAR cells line as the embryo surrogate ( Evron et al , 2011 ; Zhang et al , 2011 ; Li et al , 2017 ) found that up-regulation of AQP3 had no effect on JAR cells adhesion to HEC-1A cells (Fig. 4 Bd and Ce).…”
Section: Resultsmentioning
confidence: 97%